Model considerations on physico-chemical nature of protein-nucleic acid contacts through amino acid carboxylic groups: spectroscopic data - Samijlenko, S.P.; Kolomiets, I.M.; Kondratyuk, I.V.; Stepanyugin, A.V. (Биополимеры и клетка, 1998)
This paper generalizes the results of a series of the works on spectroscopic (IR, UV, NMR, Roman) investigations of complexes of nucleotide bases, their numerous methyl and glycosyl derivatives with amino acid carboxylic groups modeling point protein-nucleic acid contacts. The specificity of interactions between bases and two forms of carboxylic group – neutral and deprotonated – was determined. The structures of the complexes investigated were established, and the role of various atomic groups in their formation was elucidated as welt. Special consideration has been given to the frequent occurrence of proton transfer in the studied complexes. The significance of the data obtained in understanding of elementary mechanisms of protein-nucleic acid interactions is discussed.